1979
DOI: 10.1029/jb084ib14p08183
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and distribution of common ‘sand’ dunes on Mars: Comparison with the Earth

Abstract: Massed crescentic ridges are the most common dunes in the north circumpolar erg and crater floor dune fields on Mars; they are similar in plan to dunes that are typical of many desert basin ergs and dune fields on Earth. This correspondence implies that the dynamics of dune formation are similar on the two planets, despite martian constraints on dune formation that include much higher velocity winds required to move 'sand' in saltation, the possible inhibition of sand movement by absorbed water vapor and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
78
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(83 citation statements)
references
References 32 publications
(17 reference statements)
1
78
0
1
Order By: Relevance
“…However, we regard this situation as unlikely. It has long been known that the vast majority of the large Martian dunes as seen in the Viking Orbiter and Mariner 9 images are transverse in form [Breed et al, 1979], indicating that the winds strong enough to initiate saltation and form dunes are almost without exception unidirectional [Wasson and Hyde, 1983]. This is supported by the GCM calculations of wind modality made by Lee and Thomas [ 1995].…”
Section: Introductionsupporting
confidence: 64%
“…However, we regard this situation as unlikely. It has long been known that the vast majority of the large Martian dunes as seen in the Viking Orbiter and Mariner 9 images are transverse in form [Breed et al, 1979], indicating that the winds strong enough to initiate saltation and form dunes are almost without exception unidirectional [Wasson and Hyde, 1983]. This is supported by the GCM calculations of wind modality made by Lee and Thomas [ 1995].…”
Section: Introductionsupporting
confidence: 64%
“…The north polar layered deposits appear to be the source of at least some of the dark material that composes the north polar erg. Breed et al [1979] interpreted the distribution of dunes in the erg to be consistent with sediment sources in the layered terrain. The volume of the erg is much less than the estimated volume of material eroded from the layered deposits, further supporting the hypothesis that the dune material was derived from erosion of the layered deposits [Thomas, 1982; Blasius et al, 1982;Lancaster and Greeley, 1990].…”
Section: Introductionmentioning
confidence: 95%
“…In this regard, RS has been invaluable for comparing the diversity of dune morphologies between the two planets (e.g., Breed et al, 1979b;Schatz et al, 2006;Bourke, 2010). However, recent advances in the spatial resolution of image data from Mars, mainly from the High Resolution Imaging Science Experiment (HiRISE), have prompted several important contributions inferring both past and contemporary processes.…”
Section: Extra-terrestrial Dunesmentioning
confidence: 99%
“…These foundational dune classifications have been related to controlling variables such as sand supply, vegetation cover, and wind directional variability (Fryberger and Dean, 1979;Wasson and Hyde, 1983). At roughly the same time, extensive tracts of dunes were discovered on the surface of Mars during the Mariner and Viking missions (e.g., Cutts and Smith, 1973;Breed et al, 1979b;Tsoar et al, 1979). It was found that, curiously, most extra-terrestrial dunes have almost identical morphology to those on Earth.…”
Section: Introductionmentioning
confidence: 99%